Developing a Human Resource Management Model for E-Government Implementation in the Public Sector - Rasona Sunara Akbar; Triyuni Soemartono; Pandji Sukmana; T. Herry Rachmatsyah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid digital transformation in Indonesia requires public agencies to align human resource (HR) capabilities with e-government reforms. This study aims to develop a conceptual HR management model for the public sector to support effective e-government implementation. An exploratory qualitative approach was used, and a multi-level case study was conducted on the State Civil Service Agency (SAPK) and the Ministry of Law (SIMPEG). Data were obtained through in-depth interviews, document analysis, and field observations, then thematically analyzed using NVivo. The results highlight HR’s role as an enabler, integrator, and catalyst for change. SAPK and SIMPEG have improved efficiency, but challenges remain, including low digital literacy, resistance to change, fragmented policies, and limited regional budgets, which hinder interoperability and sustainability of public digital services. The proposed integrative HR management model comprises five pillars: digital competence, adaptive structure, digital governance, supporting infrastructure, and digital organizational culture. Policy recommendations include targeted digital training, integrated personnel systems, dedicated budget allocations, and HR regulatory reform. This model provides a strategic roadmap for national and regional agencies to develop a capable, efficient, transparent, and service-oriented bureaucracy in the digital era.